Puisi “Ḥanῑn” Karya Faruq Juwaidah dalam Antologi Lau Annanᾶ Lam Naftariq (Analisis Semiotika Riffaterre) / Poetry "Ḥanῑn" by Faruq Juwaidah in Lau Annanᾶ Lam Naftariq's Anthology (Riffaterre Semiotic Analysis) - Sammad Hasibuan (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
الغرض من هذا البحث هو الكشف عن المعنى الكامل من الشعر. موضوع المادة التي تجري دراستها هو الشعر بعنوان "حنين" لفاروق جويدة وهي جزء من مختارات "لو أننا لم نفترق". الطريقة المستخدمة في هذا البحث هي المنهج الوصفي التحليلي باستخدام المنهج السميوطيقي لريفاتير. هو يقدم خطوات لفهم المعنى الكامل من الشعر أي من خلال القراءة الإرشادية والقراءة التأويلية ثم تحديد النموذج والفاريان والمصفوفة وتحديد .hypogram وأظهرت النتائج أن معنى الشوق كما يقصده الشاعر في شعر حنين هو الشوق إلى البلد أو الوطن باعتباره حبا للوطن. الى جانب ذلك  يختلف موضوع فاروق في هذه الشعر عن موضوع المعتاد وهو الحب والرومانسية. المصفوفة في هذه الشعر هي وفاء الاحتياجات الفسيولوجية (المأوى) في خطاب أبراهام ماسلو في علم النفس الإنساني.الكلمات المفتاحية:  فاروق جويدة;  شعر حنين; لو أننا لم نفترق; سميوطيقا لريفاتير Abstract:The purpose of this study is to reveal the full meaning of a poem. The object of material being studied is a poem entitled Ḥanȋn by Faruq Juwaidah which is a part of the anthology Law Annanȃ Lam Naftariq. The method used in this research is descriptive-analytical method with the Riffaterre semiotic approach. Riffaterre offers stages to understand the integrity of the meaning of a poem, namely through heuristic reading, hermeneutic reading, determining models, variants and matrices, and determining the hypogram. The results showed that the meaning of longing as meant by poets in Ḥanȋn's poetry is longing for the hometown or the country of origin as an attitude of love for the country. Apart from that, Faruq's theme in this poem is different from his usual theme, namely love and romance. The matrix in this poem is the fulfillment of physiological needs (shelter) in Abraham Maslow's Humanistic psychology discourse.